ANALISIS KEMATANGAN KARIR PESERTA DIDIK KELAS VIII SMP NEGERI 03 PONTIANAK TAHUN 2020 - Widiyarsih Widiyarsih; Yuline Yuline; Indri Astuti (Universitas Tanjungpura, 2021)
AbstractThis study was aimed to look at the characteristics of students who lack career maturity, the factors that cause students who lack career maturity and the efforts of Guidance and Counseling teachers in dealing with students who lack career maturity at SMP Negeri 03 Pontianak in 2020. Research methods used qualitative descriptive with a case study approach. The subjects in this study were three students who lack career maturity. Data collection techniques used questionnaires and interviews. Based on the results of research that has been done, there were characteristics of students who lack career maturity, namely in choosing career choices not based on interests, hesitating in making career choices, and unable to make their own decisions. The factors that cause students to lack career maturity were interested factors, peer factors, parental factors, and economic factors. Guidance and Counseling teachers' efforts in helping students who lack career maturity were providied information services, group counseling.Keywords:Analysis, Career Maturity, Students